Adherence to the Porto Criteria Based on the Hungarian Nationwide Pediatric Inflammatory Bowel Disease Registry (HUPIR) - Müller, Katalin E.; Dezsőfi, Antal; Cseh, Áron; Szűcs, Dániel; Vass, Noémi; Nemes, Éva; Kadenczki, Orsolya; Tárnok, András; Szakos, Erzsébet; Guthy, Ildikó; Kovács, Márta; Karoliny, Anna; et al. (Frontiers in Pediatrics, 2021)
Objectives: According to the Porto criteria, upper endoscopy and ileocolonoscopy with histology for patients with paediatric inflammatory bowel disease (pIBD) are recommended with small bowel imaging (SBI). We aimed to evaluate the adherence to the Porto criteria and biopsy sampling practice and to evaluate the diagnostic yield of magnetic resonance enterography (MRE) in a nationwide cohort of patients with pIBD. Methods: Newly diagnosed pIBD cases (aged 0–18 years) are registered in the prospective, nationwide Hungarian Paediatric IBD Registry (HUPIR). We evaluated the diagnostic workup of patients recorded between 1 January 2007 and 31 December 2016. Results: Data for diagnostic workup were available in 1,523 patients. Forty percent of the cases complied with the Porto criteria. Adherence to the Porto criteria increased significantly from 20% to 57% (p<0.0001). The most frequent reason for incomplete diagnostic workup was the lack of SBI (59%). In 2007, 8% of the cases had a biopsy from all segments, and this rate reached 51% by 2016 (p<0.0001). We analysed the diagnostic yield of MRE in 113 patients (10.1%) who did not have any characteristic lesions of Crohn’s disease. MRE was positive for the small bowel in 44 patients (39%). Conclusions: Adherence to the Porto criteria increased significantly during the 10-year period. This is the first study to report multiple biopsy sampling as a less accepted recommendation. The diagnostic yield of MRE in patients without characteristic lesions for Crohn’s disease was 39%.